x^2-y^2-(x+y)^2
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 07:59:17
x^2-y^2-(x+y)^2x^2-y^2-(x+y)^2x^2-y^2-(x+y)^2=x^2-y^2-x^2-y^2-2xy=-2xyx²-y²-(x+y)²=x&
x^2-y^2-(x+y)^2
x^2-y^2-(x+y)^2
x^2-y^2-(x+y)^2
=x^2-y^2-x^2-y^2-2xy=-2xy
x²-y²-(x+y)²
=x²-y²-x²-2xy-y²
=-2y²-2xy
=-2y(y+x)
(x+y)(x-y)-(x+y)^2
=(x+y)(x-y-x-y)
=-2y(x+y)
x-y/x-x+y/y-(x+y)(x-y)/y² y/x=2
(x-y)(x-y)2(y-x) (x+2y-?)(x-2y+?)
化简y(x+y)+(x+y)(x-y)-x^2
(x-2y)(x+y)+(x+y)计算
计算:(x-y)^2-(x+y)(x-y)
2(x-y)²-3(x-y)(-y-x)
(x+y)(x-y)-(x-y)^2如题 (x+y)(x-y)-(x-y)^2
【2(x-y)(x-y)(x-y)-8(x-y)(x-y)(x+y)+6y(x-y)(x-y)]/2(x-y)(x-y)
(x-y/x+2y)³
因式分解x(x+y)(x-y)-x(x+y)^2
[(x-y)^2-(x+2y)(x-2y)]/y
计算:y-x分之x+y+x-y分之y-y-x分之2x-y
求因式分解(x-y)²-2(x-y)³和(x+y)(x-y)-x(x-y)
化简 (x+2)平方-(x-y)(y-x)是(x+y)平方-(x-y)(y-x)
x根号x+x根号y/xy-y^2)-(x+根号xy+y/x根号x-y根号)y
[(x+2y)²-(x+y)(x-y)-7y²】÷(2y)
{(x²+y²)-(x-y)+2y(x-y)}/4y
x^2(x-y)+(y-x)